Legal Protection for Wife and Child as Consequence of Head of Family’s Criminal Imprisonment Enforcement - Rini Fitriani; Liza Agnesta Krisna; Muhammad Natsir; Zulfiani Zulfiani (Volksgeist: Jurnal Ilmu Hukum dan Konstitusi, 2023)
One area of increasing narcotics distribution and abuse was the coast of East Aceh, Aceh Province. This led to heads of household becoming prisoners. The head of household’s imprisonment directly affected their families’ welfare. The wives would be forced to replace the heads of household’s role despite their limited education, skills and capital for performing business. This research aimed to examine the protection for women (wives) and children; and the effort local government could do to legally protect these wives and children. This was juridical empirical research, which aimed to study the prevailing provisions of law what occurred factually in the community. Protecting and securing wife and child’s welfare due to head of household undergoing imprisonment was the state’s obligation through local government to prevent non-optimal fulfillment of wife and child’s rights. Protection efforts were done to satisfy wife and child’s welfare by allocating certain fund in specific-purpose aid for child’s education and welfare other than the Social Department’s BLT (cash transfer) aid. Geuchik (head of village) were to proactively coordinate with the PPPA department of East Aceh Regency in managing special aid to fulfill the wives and children’s welfare in a situation of case a quo.